Responsible investments in life insurers' optimal portfolios under solvency constraints - Sebastian Schlütter; Emmanuel Senyo Fianu; Helmut Gründl (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2022)
Socially responsible investing (SRI) continues to gain momentum in the financial market space for various reasons, starting with the looming effect of climate change and the drive toward a net-zero economy. Existing SRI approaches have included environmental, social, and governance (ESG) criteria as a further dimension to portfolio selection, but these approaches focus on classical investors and do not account for specific aspects of insurance companies. In this paper, we consider the stock selection problem of life insurance companies. In addition to stock risk, our model set-up includes other important market risk categories of insurers, namely interest rate risk and credit risk. In line with common standards in insurance solvency regulation, such as Solvency II, we measure risk using the solvency ratio, i.e. the ratio of the insurer's market-based equity capital to the Value-at-Risk of all modeled risk categories. As a consequence, we employ a modification of Markowitz's Portfolio Selection Theory by choosing the "solvency ratio" as a downside risk measure to obtain a feasible set of optimal portfolios in a three-dimensional (risk, return, and ESG) capital allocation plane. We find that for a given solvency ratio, stock portfolios with a moderate ESG level can lead to a higher expected return than those with a low ESG level. A highly ambitious ESG level, however, reduces the expected return. Because of the specific nature of a life insurer's business model, the impact of the ESG level on the expected return of life insurers can substantially differ from the corresponding impact for classical investors.
Keywords: G11; G22; G32; 330; Socially responsible investments; Life insurance companies; Portfoliooptimization; Solvency regulation